Pengaruh Penggunaan Media Pembelajaran ICT terhadap Hasil Belajar IPA Kelas V di SD Lanraki II Makassar - Nur Syam; Fitriyani Yahya; Mulyadi Mulyadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstract: The Effect of Using ICT Learning Media on Class V Science Learning Outcomes at Sd Lanraki I I Makassar. This study aims to determine the influence of the use of ICT learning media on the learning outcomes of science class V at SD Lanraki II Makassar. The approach to this study uses experimentalresearch used to determine the successful use of ICT Learning media. The population of this study was all grade V students of SD Lanraki II, while the study sample was 17 people. Data collection is carried out by observation, learning outcomes tests and documentation. The data collected in the study were analyzed using descriptive and inferential statistical techniques. Based on the results of data analysis, it can be seen that the results of the school environment questionnaire of 2180 and the results of the character building questionnaire of 2227 can be seen that the results of ICT-based learning affect the science learning outcomes of grade IV students of SD Inpres Lanraki 2 Makassar City. Judging from the results of the paired sample t-test, the significance value was obtained by 0.000< 0.05.